Computer-mediated communication attributes and life satisfaction among adolescents in Malaysia - Ang, Chin Siang (2014)
Computer-mediated communication (CMC) can be influential advocates for interpersonal relationship transactions, playing a critical social platform in encouraging adolescents to express emotional freedom and to develop social skills. Despite data indicating that adolescents’ involvement in CMC contributes to positive psychological development, the nature and extent of these attributes, and how it relates to life satisfaction remained uncertain. Utilizing Theories of Uses and Gratifications and Self-determination as a major framework, this thesis aimed to: (a) examine a hypothesized model linking CMC attributes (attitude toward online relationship formation, internet habit strength, online communication, online selfdisclosure, and psychological need satisfaction in online friendships) to life satisfaction, (b) examine the mediating roles of online communication and online self-disclosure in the links between the attitude toward online relationship formation, internet habit strength, and psychological need satisfaction in online friendships, and (c) examine the moderating roles of age, gender, and loneliness in such hypothesized model. There were 1572 participants, and the participants were 13-year-old to 18-year-old secondary students who completed a series of validated questionnaires containing self-reports of loneliness, CMC attributes, and life satisfaction. The technique of Structural Equation Modelling (SEM) was applied to investigate the hypothesized model. Results indicated that direct links between attitude toward online relationship formation, internet habit strength, and psychological need satisfaction in online friendships. This study also reported direct links between online communication, online self-disclosure and psychological need satisfaction in online friendships, and also a direct link between psychological need satisfaction in online friendships and life satisfaction. Bootstrapping procedures further provided evidence that online communication and online self-disclosure emerged as significant partial mediators in the link between the attitude toward online relationship formation and psychological need satisfaction. In this pattern of links, both mediators were equally strong. Likewise, online communication and online self-disclosure also emerged as significant partial mediators in the link between internet habit strength and psychological need satisfaction. For this pattern of links, both mediators differed significantly in strength. In particular, online communication emerged as a stronger mediator than online selfdisclosure. Multigroup analyses revealed that age, gender, and loneliness acted as significant moderators in the links between CMC attributes and life satisfaction: (a) the positive links between internet habit strength, online self-disclosure, and psychological need satisfaction were observed for younger adolescents only, (b) the positive links between attitude toward online relationship formation and online communication, and between psychological need satisfaction and life satisfaction were stronger for male adolescents than female adolescents, whereas the positive link between internet habit strength and online self-disclosure was observed for female adolescents only, and (c) the positive link between attitude toward online relationship formation and psychological need satisfaction was stronger for the lonely group rather than the nonlonely group. The results highlight the importance of assessing CMC attributes in conjunction with age, gender, and loneliness when studying adolescents’ life satisfaction. The study findings suggest that CMC context may serve as a new social milieu for adolescent subjective well-being.